Milton and the Jews - Brooks, Douglas A. (Cambridge University Press, 2008)
The issue of the Jews deeply engaged Milton throughout his career, and not necessarily in ways that make for comfortable or reassuring reading today. While Shakespeare and Marlowe, for example, critiqued rather than endorsed racial and religious prejudice in their writings about Jews, the same cannot be said for Milton. The scholars in this collection confront a writer who participated in the sad history of anti-Semitism, even as he appropriated Jewish models throughout his writings. Well grounded in solid historical and theological research, the essays both collectively and individually offer an important contribution to the debate on Milton and Judaism. This book will be of interest not only to scholars of Milton and of seventeenth-century literature, but also to historians of the religion and culture of the period.